Factors of consumer behavior in the purchase process of Peruvian bodegas in the context of COVID-19 - Palacios, Patricia; Rosado, Herlin; Tolentino, Leddy; Vicente-Ramos, Wagner (Business: Theory and Practice, 2022)
The objective of the research was to determine the factors of consumer behavior that influence the purchase process of bodegas in the context of COVID-19 in the year 2021. The study was carried out from the quantitative approach, with a research design non-experimental-transversal-explanatory. A questionnaire consisting of 31 questions was applied to 399 consumers who attended Peruvian bodegas, who were randomly selected for the application of the instrument. The results generated by structural equations show that social factors and psychological factors of consumer behavior significantly influence the purchase process (p < 0.05); however, unlike the previous results, the cultural factors of consumer behavior do not have significant implications in the purchase decision (p value = 0.054 < α = 0.05) and in the feeling after the purchase (p value = 0.082 < α = 0.05), as well as the personal factors of consumer behavior do not have significant implications in the activity prior to the purchase (p value = 0.456 < α = 0.05). The conclusion of the research mentions that the factors of consumer behavior have an influence on the purchase process, however, some factors show a greater impact in the study.